Rotating horizontal convection with meridional ridges - Zhang, Yu; Zhang, Zhengguang; Wang, Wei (Frontiers in Marine Science, 2022)
According to recent studies, the large-scale effect of bottom topography on the ocean overturning circulation can be considered as a result of bottom enhancement of turbulent mixing in the abyssal ocean. Here we show, using laboratory experiments of rotating horizontal convection, that even without spatial variation of mixing intensity, oceanic meridional ridges can strongly impact both the strength and the pattern of the overturning in some fundamental ways. For example, as suggested by experimental results, the existence of the mid-Atlantic ridge can lead to the formation of another deep jet, like the deep western boundary current (DWBC), along the ridge’s eastern edge as a pathway for southward export of newly formed deep water. In response to this interior (mid-basin) jet and the associated isopycnal displacement, adiabatic flow structures may occur in upper and lower layers, including two opposing jets located respectively above and below the interior DWBC. Though unable to contribute to the overturning, they can probably affect transport along isopycnals. In the latitudinal band of the Antarctic Circumpolar Current without side boundary but with multiple ridges lying over the bottom, multiple interior DWBCs may develop preferentially along higher ridges, carrying the Antarctic Bottom Water into the northern latitudes. Moreover, the overturning cell or the strong jets can migrate vertically with the grow or decay of the ridge. Therefore, presumably strong variations of both ocean circulation and stratification may have occurred more than once during the past millions of years, as consequences of plate tectonic evolution, and have caused substantial changes of earth climate.